The LungPath study: variation in the diagnostic and staging pathway for patients with lung cancer in England. Issue 3 (15th July 2015) - Cane, Paul; Linklater, Karen; Santis, George; Møller, Henrik; Peake, Michael
Abstract : The LungPath project investigated differences in lung cancer diagnostic practice by following the diagnostic pathways of 1507 patients from 19 representative English lung cancer centres. We found large variation in the proportion of patients receiving positron emission tomography-CT scan (range 13%–64%) and endobronchial ultrasound (range 2%–31%). There was also wide variation in the proportion of patients with good performance status who had their tumours histologically confirmed (range 61%–100%). The variation is discussed with reference to current national guidelines and implications for patient care.